PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN NILAI-NILAI KARAKTER SISWA KELAS X MIA SMA NEGERI 12 PEKANBARU TAHUN PELAJARAN 2014/2015 - Zul Arifin; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of group counseling services to increase the values of character class X MIA SMA 12 Pekanbaru school year 2014/2015. This research was conducted in SMA 12 months Pekanbaru from March 2015 to May 2015. The method used was experimental method to pattern one-group pretest-posttest. That is the subject in the study were a number of students of class X SMA Negeri 12 Pekanbaru MIA totaling 30, the subject of research in select purposively in accordance with the characteristics of the subjects to be researched is the practice that has the character values are lowest. Instrument in this study was a questionnaire about the practice of the values of the characters. This questionnaire consists of 40 items on the practice of the values of character with alternative "yes" and "no" and then the data is processed with statistics. The hypothesis proposed is: 1.Terdapat difference in the practice of the values of significant characters before with after the implementation of group counseling to students 2.Terdapat significant positive effect of group counseling services to the increasing practice of the values of the character of the students .. From the research conducted, by using the t test obtained t of 12.5 and ttable of 2,021. So, thitung> ttable (12.5> 2.021). Which means that in this study are differences in the practice of the values of significant characters before with after the implementation of group counseling. From the calculation of product moment correlation Koofesien Determinants known or r2 = 0.39 which means there is a 39% contribution to the improvement of guidance services practice group values MIA character class X SMA Negeri 12 Pekanbaru school year 2014/2015.Keywords: Effect of Group Guidance, Values Character